Supporting student nurse professionalisation: The role of the clinical teacher - Brown, Janie; Stevens, J.; Kermode, S. (Churchill Livingstone, 2012)
This paper reports aspects of the findings from the qualitative component of a mixed methods research study that investigated the role of the Clinical Teacher in student nurse professional socialisation. Graduates and Clinical Teachers were interviewed to identify the domains where the support of a Clinical Teacher was crucial in the students' development of a professional identity. Emergent themes were clustered into seven (7) domains as follows: Professional role concept; Acculturation; Acquisition of Knowledge; Acquisition of Skill; Acquisition of Professional Values; Assimilation into the Organisation; and a seventh domain encompassing the role model attributes of Clinical Teachers. The domains are presented alongside exemplars from the interviews, in order to illustrate the importance of the support of a Clinical Teacher.